PELAKSANAAN BERJAPA SEBAGAI STRATEGI PEMBENTUK BUDHI PEKERTI SISWA DI SMK PRSHANTI NILAYAM KECAMATAN KUTA KABUPATEN BADUNG - Wayan Siskasari; I Wayan Winaja; I Nyoman Winyana (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
The teachings of Hinduism as stated in the holy book Veda are a guide for Hindus to live a holy life. However, along with advances in science and technology (IPTEK), Hindus have paid less attention to the sacred teachings of the Vedas, Advances in science and technology in this era of globalization have resulted in many changes in various aspects of life, both economic, social and cultural. Advances in science and technology have indeed brought changes to material prosperity, However, it is necessary to think about the negative impacts caused by the development of science and technology, especially the decline in character in adolescence. To prevent these negative influences, through formal activities (at school) especially in improving students' morals, Therefore, Hindu religious teachers, especially at Prshanti Nilayam Vocational School, provide a deeper spiritual understanding through chanting activities. Chanting is a form of spiritual activity by chanting a mantra or God's name repeatedly, By doing Japa, it is believed that you can eliminate mental impurities such as lust, anger, greed and so on. So Sadu Gunawan is the one who shapes the child's personality into a Suputra child with noble character. Based on the background above, there are three problem formulations obtained, including: (1) Why is the implementation of chanting a strategy for forming Budhi Character education at Prshanti Nilayam Vocational School, Kuta District, Badung Regency? (2) How does the process of implementing chanting a strategy for forming Budhi Character education at Prshanti Nilayam Vocational School, Kuta District, Badung Regency? (3) What are the implications of the implementation of chanting a strategy for forming Budhi Character education in religious practice at Prshanti Nilayam Vocational School, Kuta District, Badung Regency? The theories used to analyze this problem formulation are: Constructivism theory, Structural Functional theory, and Value theory. The subjects of this research were students of Prshanti Nilayam Vocational School, Kuta District, Badung Regency. The methods used to collect data are: observation method, interview method, literature study, and documentation method. The data that has been collected is analyzed using a qualitative descriptive analysis method with reduction steps, data presentation and drawing conclusions. The research results show (1) The form of chanting has a multifunctional form and is very useful for improving moral character and increasing sradha and devotional service towards Ida Sang Hyang Widhi Wasa (God Almighty). (2) The process of implementing japa. Hindu religious teachers act as coaches for students by applying the rules for chanting. The mantra used is the Vaikhari Japa method, namely by using mantras including the Gayatri Mantra or Savitri Mantra, Pancaksara Siva Mantra, and Saraswati Mantra. (3) There are implications of Hindu religious education that is instilled through the implementation of Japa, including the growth of faith and devotion towards Ida Sang Hyang Widhi Wasa, the development of ethical values or behavior (morals), the growth of an attitude of sacrifice (Yadnya), and there are also several implications for Hindu religious teachers in teaching, namely being disciplined, efficient, honest, creative, friendly, and compassionate.